Genetic interactions patterning the Tribolium fate map - Zhu, Xin (Kansas State University, 2014)
A segmented body plan is conserved in vertebrates and arthropods. Comparative studies implicate a conserved mode of A-P axis patterning and segmentation among vertebrates: Wnt signaling is involved in fate map patterning along the A-P axis and in segmentation in the posterior region of the embryo. On the other hand, comparative studies in arthropods have revealed distinct modes of development between long and short germ insects, which differ both morphologically and genetically. In the short germ insect Tribolium, a Wnt activity gradient contributes to A-P axis patterning and generates a posterior Tc-cad expression gradient that regulates segmentation through a pair-rule gene clock, forming segments sequentially as in vertebrates. In contrast, instead of Wnt activity, a hierarchy of regulatory genes regionalizes the blastoderm and defines segments simultaneously in the long germ insect Drosophila. In Tribolium, Tc-zen-1, Tc-otd-1 and Tc-cad play key roles in patterning serosa, head and trunk regions, respectively, of the blastoderm fate map, which are impacted by changes in Wnt activity levels. However, interactions between these genetic factors have not been described. My work revealed that cross talk between the Wnt and Dpp signaling pathways regulates the expression of Tc-zen-1 to determine the serosa. Furthermore, mutually repression between Tcotd-1 and Tc-cad defines the head and trunk regions while mutual repression between Tc-zen-1 and cad determines the posterior extent of the dorsal serosa. Analysis of target genes of the posterior Tc-cad gradient indicates that the Tc-cad gradient regulates the serial expression of gap genes, which are predominately regulators of Hox genes. Thus the posterior Tc-cad gradient determines segment formation through regulation of pair-rule genes in the insect segmentation clock, and defines segmental identity through regulation of gap genes. Given its effect on Tc-zen-1 and Tc-cad, the Wnt activity gradient is a key organizer of the Tribolium blastoderm fate map. Since homologs of these genes as well as the Wnt signaling pathway have also been identified in several other short germ band insects, and affect cell fates along the A-P body axis, this work provides a new paradigm for the short germ mode of development to guide studies in other arthropods.
Keywords: Tribolium castaneum; Wnt signaling pathway; Fate map; Cad gradient